Psychological relationship of students' logic and reasoning skills in the context of critical thinking - Ж. Молбасынова; Ю. Гелишли; М. Мурзагулова; У. Жамирова; A. Даникеева (Хабаршы. Психология және социология сериясы)
In the article, one of today's actual issues is in the direction of supporting new ideas proposed by young intellectuals In the context of critical thinking, the theoretical and methodological bases of the psychological relationship between students' logic and reasoning skills were studied. In this direction, the concepts of "thinking", "critical thinking", "logic", "reasoning skills", "psychological relations of students' logic and reasoning skills on the basis of critical thinking " were defined , which allow for theoretical justification through a review of philosophical, psychological and pedagogical scientific literature.